Improvement of Fiqh Lesson Through The Fathul Qorib Study - Muhammad Fodhil; Ema Siti Nur Azizah (SCHOOLAR: Social and Literature Study in Education, 2021)
Learning fiqh is one of the foundations in everyday life especially for Muslims, Learning fiqh using the book Fathul Qorib at the Darul Ulum Islamic Boarding School in 1885, so that learning the book of fathul qorib has become an obligation that must be developed until now, as the way of delivery, namely to improve the learning of fiqh material so that students are able to understand, translate, interpret and solve a problem that is in the book of Fathul Qorib. This article is a case study with a qualitative approach, the result of this research is to increase the understanding of fiqh material through the study of the fathul qorib book at Madrasah Diniyah Pondok Pesantren Darul Ulum Peterongan. In the process of increasing the understanding of the students, namely by using the sorogan, bandongan, and practice methods, discussions and lectures. So this learning method aims so that students can read, translating and explaining fiqh material through the study of the book Fathul Qorib using his own language, The teacher also strengthens students' understanding in the science of nahwu and shorof so that students can read the book of fathul qorib without any harokats and meaning.